Ninth Five Year Plan (1997-2002) and Annual Plan 1997-98 Volume-I Government of Manipur - Planning Commission (Planning Commission, 1997)
Manipur has a total area of 22,327 Sq. Km of which one-tenth consists of hills and only one-tenth comprises the valley. It is one of the border states in the north eastern part of the country having an international boundary of about 352 kms. long stretch of land with Myanmar on the east. It is bounded by Nagaland on the north, Assam on the west and Mizoram on the south. The state is land-lock and it does not have any waterways transport system to link with other states of the country.
Government of Manipur, Planning Department